EFFECT OF ADDITION OF DIFFERENT LEVELS OF MOLASSES AND LIQUID WHEY ON FERMENTATION CHARACTERISTICS OF DATE PALM PHOENIX DACTYLIFERA LEAVES SILAGE AND ITS NUTRITIVE VALUE - & et al., Saeed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
Factorial experiment was carried out to investigate the effect of two factors, molasses (M) and liquid whey (LW) on fermentation characteristics and nutritive value of date palm leaves (DPL). Fresh DPL was chopped into 1-2 cm and treated with treatment solutions prepared by addition of 5, 7.5 or 10% of M together with 3 levels of LW on basis of nitrogen content equivalent to 0, 1 or 1.5% of urea. Ground wheat straw was added to each sample at rate of 50 g. Materials were packed into double nylon sacs and ensiled for 60 days. Samples of DPL were appeared firmly connected and most of them acquired yellowish to light green color with emission of an apple-date vinegar smell. Results revealed that there was a significant (P˂0.01) decrease in dry matter and crude fiber contents with increasing M levels. In DPL silages prepared with 10% of M, these contents were 30.04 and 34.70% respectively. Crude protein content was significantly increased (P˂0.01) from 6.39 to 7.32 and 7.32% for 0, 1 and 1.5% levels of LW respectively. This was associated with a significant (P˂0.05) decrease in fat content. All samples of DPL silages were characterized with good quality as evidenced by fermentation characteristics. There was a significant (P˂0.01) decrease in pH accompanied with an increase (P˂0.01) in ammonia nitrogen concentration. Values ranged between 3.85 to 3.78 and 3.84 to 4.32% of total nitrogen for the 1st and 2nd parameters due to the addition of low and high levels of M respectively. Addition of LW at 1 and 1.5% levels decreased (P˂0.05) pH from 3.85 to 3.81 and 3.81, but concentrations of total volatile fatty acids were increased (P˂0.01) from 2.29 to 2.97 and 3.11% of DM. Results showed that increasing level of M to 7.5 and 10% increased (P˂0.01) DM loss from 12 to 17.78%, but it improved (P˂0.01) aerobic stability. Samples of DPL silages prepared with addition of 1.5% of LW resisted for longer (P˂0.01) period (55.58 hours) before signs of aerobic deterioration were appeared.